2017
DOI: 10.3390/e19040141
|View full text |Cite
|
Sign up to set email alerts
|

Permutation Entropy for the Characterisation of Brain Activity Recorded with Magnetoencephalograms in Healthy Ageing

Abstract: Abstract:The characterisation of healthy ageing of the brain could help create a fingerprint of normal ageing that might assist in the early diagnosis of neurodegenerative conditions. This study examined changes in resting state magnetoencephalogram (MEG) permutation entropy due to age and gender in a sample of 220 healthy participants (98 males and 122 females, ages ranging between 7 and 84). Entropy was quantified using normalised permutation entropy and modified permutation entropy, with an embedding dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Nevertheless, similar to EEG, MEG analysis at the sensor level is affected by volume conduction, although to a much smaller degree [ 12 ]. MEG data have been used to: identify epileptic zones [ 13 ], investigate brain function, evaluate neurofeedback [ 14 ], determine the effects of pathology, investigate effect of cognitive decline [ 15 ], and, to determine the effects of ageing on the brain [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, similar to EEG, MEG analysis at the sensor level is affected by volume conduction, although to a much smaller degree [ 12 ]. MEG data have been used to: identify epileptic zones [ 13 ], investigate brain function, evaluate neurofeedback [ 14 ], determine the effects of pathology, investigate effect of cognitive decline [ 15 ], and, to determine the effects of ageing on the brain [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once the brain recordings are obtained, a wide range of linear and non-linear and processing techniques, such as causality [ 17 ], entropy [ 16 ], synchronisation [ 18 ], correlation [ 19 ], and complexity [ 4 ], can be applied to them. Complexity is a concept stemming from non-linear analysis methods that could be applied to evaluate changes in brain activity recorded in MEG signals (see [ 20 ] for a detailed description of complexity).…”
Section: Introductionmentioning
confidence: 99%
“…However, our results do not depend on the temporal scales, but they reflect the changes in all the frequency bandwidth and are consistent across spatial scales. Increased complexity of MEG signals with age were also reported in [8] and [9]. Evidences of aging-related changes in the Fourier spectrum of EEG with a decrease in power for low frequencies and an increase for high frequencies were also reported in [38], [39], [40].…”
Section: Discussionmentioning
confidence: 78%
“…Fernández et al found significant increases in Lempel-Ziv complexity measures with age [8]. Shumbayawonda et al confirmed increases in permutation entropy with age [9], and in permutation Lempel-Ziv complexity with age [10]. By contrast, Coquelet et al did not find any significant agerelated changes in both static and dynamic power envelopebased connectivity from resting-state MEG data, suggesting that the electrophysiological connectome is maintained in healthy aging [4].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, our correlation analysis showed that higher complexity values over highly overlapping regions to the ones mentioned above were associated with larger hippocampal volumes only in females. Different techniques were applied over the years to acquire more information related to the differences between males and females on the activity of the brain [39,[41][42][43][44]. Detection of these sex differences is not a trivial task as male and female activity in MEG signals is very similar, especially for healthy subjects.…”
Section: Discussionmentioning
confidence: 99%